Risk of malignancy in patients with psoriasis: a 15‐year nationwide population‐based prospective cohort study in Korea - Lee, J.W.; Jung, K.J.; Kim, T.G.; Lee, M.; Oh, J.; Jee, S.H.; Lee, M.G. (Journal of the European Academy of Dermatology and Venereology, 2019)
Background The association between psoriasis and risk of malignancy has not been thoroughly evaluated in a large longitudinal cohort of Asian population. Objective To determine the long‐term risk of malignancy in Korean adult patients with psoriasis. Methods We conducted a nationwide population‐based prospective cohort study with a 15‐year observational period. During the baseline period (1997–2000), total 1 773 786 Korean subjects who received health insurance from the National Health Insurance System were enrolled and 5788 subjects were defined as a psoriasis group. The number of new‐onset malignancy was collected during the observational period (2001–2015). Results Patients with psoriasis had a higher adjusted hazard ratio (aHR) for development of overall malignancy [aHR 1.08, 95% confidence interval (CI) 1.00–1.18] and gastric cancer (aHR 1.31, 95% CI 1.08–1.58) compared to controls. The risks of non‐Hodgkin lymphoma and non‐melanoma skin cancer were significantly increased only in patients with psoriasis who received systemic treatments (aHR 2.86, 95% CI 1.07–7.61 and aHR 3.93, 95% CI 1.47–10.47, respectively). Conclusion Psoriasis is associated with long‐term risk for overall malignancy in Koreans, which was primarily driven by the increased risk of gastric cancer.